P3_9 The Loudest Sound - Chatwin, Oliver; Holtom, Josh; Iorga, Adriana; Tyler, Saffron (Physics Special Topics, 2020)
This paper looks at using the sound level of two famous explosions, Tunguska and Krakatoa, to estimate their energies. It is found that the events had energies of 1.37 · 1029J and 5.09 · 1029J respectively, which are found to be drastic over-estimates. The reasons for this are discussed.